Representaciones sociales de la justicia en un grupo de usuarios y de no usuarios de las Casas de Justicia en Medellín (2010)
ABSTRACT: This paper is based on an early study´s results. On this early study the social representation of justice and its relationship to social practices and forms of conflict resolution in users and nonusers (involved and not involved) of the Houses of Justice in Medellin where identified. Through the technique of words evoaction it eas possible to gain access to the semantic field developed aroud the idea of "justice", and to identify the core elements of its representaion. finally, it was possible to develop hypothesis about the organization of justice, and to describe them according to their type of involvement with the practice of conflict resolution.